How to teach immune response? A proposal from immunology for the training of the general practitioner - Daynelis Pardo Martínez; Luis Alberto Mass Sosa; Yosvany Castillo Leyva (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The Cuban medical school has faced, for several decades, the challenge of a developing education and the demands of an educational process that has a similar nature. Numerous subjects throughout the career approach immunology, being a transdisciplinary science. However, the biased and static view of each of these disciplines can lead to errors of interpretation in the students. In this work, an approach of the immune response is proposed as a dynamic and complex event and not as the mere concept of "lines of defense" .In, this way a model is created that allows the student interpreting phenomena of other disciplines based on the dynamics of the immune response as a fundamental law of immunology.